Digital Contact Tracing: The Medium is the Message - Gunkel, David Joseph (Rizoma, 2020)
This essay investigates digital media devices and networks for addressing the spread and control of the novel coronavirus/COVID-19 infection. But unlike many of the other essays in this special issue, it will not focus on the message — the information and misinformation, the accurate reportageand the rumors, or the news and the fake-news— that is conveyed onthese digital platforms. Instead, I will focus on the use of digital mobile devices and networks to monitor and control the social aspectsof the virus and the vectors of infection. Toward this end, we will considerthe different ways that mobile technology can be employed to address and respond to a global pandemic like COVID-19; and we will examine the opportunities and challenges of DCTT in an effort not just to understand how these technologies work but to extract from this analysis a clear formulation of their possible benefits and attendant costs.